Concepts in Cell Biology - History and Evolution (Plant Cell Monographs,, 2018)
This book discusses central concepts and theories in cell biology from the ancient past to the 21st century, based on the premise that understanding the works of scientists like Hooke, Hofmeister, Caspary, Strasburger, Sachs, Schleiden, Schwann, Mendel, Nemec, McClintock, etc. in the context of the latest advances in plant cell biology will help provide valuable new insights. Plants have been an object of study since the roots of the Greek, Chinese and Indian cultures. Since the term "cell" was first coined by Robert Hooke, 350 years ago in Micrographia, the study of plant cell biology has moved ahead at a tremendous pace. The field of cell biology owes its genesis to physics, which through microscopy has been a vital source for piquing scientists' interest in the biology of the cell. Today, with the technical advances we have made in the field of optics, it is even possible to observe life on a nanoscale. From Hooke's observations of cells and his inadvertent discovery of the cell wall, we have since moved forward to engineering plants with modified cell walls. Studies on the chloroplast have also gone from Julius von Sachs' experiments with chloroplast, to using chloroplast engineering to deliver higher crop yields. Similarly, advances in fluorescent microscopy have made it far easier to observe organelles like chloroplast (once studied by Sachs) or actin (observed by Bohumil Nemec). If physics in the form of cell biology has been responsible for one half of this historical development, biochemistry has surely been the other.